OP0304 Efficacy of Hydroxychloroquine in Primary Hand Osteoarthritis: A Randomized, Double-Blind, Placebo Controlled Trial. (9th June 2015) - Basoski, N.; Lee, W.; Ruijgrok, L.; Kloppenburg, M.; Boxma, B.; Kok, M.R.; Weel, A.E.
Abstract : Background: Current pharmacological treatment options of hand osteoarthritis (hand OA) are limited. Hydroxychloroquine (HCQ) has been used successfully in the treatment of mild rheumatoid arthritis and other auto-immune diseases for many years and is believed to be beneficial in hand OA as well. Objectives: The main objective was to study the symptom modifying effect of HCQ in primary hand OA Methods: We conducted a randomized, double blind, placebo controlled multi center trial in which patients ≥40 years of age, with primary hand OA according to the ACR classification criteria were included. Patients with ≥1 hand joint with a Kellgren and Lawrence grade 4 were excluded. Hand pain symptoms, independent of level of severity, had to be present for at least one year. Patients were randomly assigned to receive either hydroxychloroquine 400 mg once a day or placebo during a treatment period of 24 weeks. Paracetamol was used as rescue medication and patients were allowed to continue all comedication except NSAIDs during the study. If patients were using NSAIDs, inclusion was allowed after a wash out period of 1 week. The primary outcome was decrease of hand pain in the previous 24 hours on a 100 mm visual analogue scale (VAS) at the end of the study. Secondary outcomes included change in total score of the Australian Canadian Hand Osteoarthritis Index (AUSCAN) and the Arthritis Impact Measurement Scale 2 SF (AIMS2-SF) at the end of the study. Results: Two hundred and two patients were included from July 2010 till December 2013. Six patients who were lost to follow up at an early stage of the study (i.e. no data at any time point), were excluded from the analysis. An intention to treat analysis was performed on the remaining 196 patients (HCQ n=98, placebo n=98). No differences were seen in baseline characteristics between the groups: 86% of the patients were female, the mean age was 57 years. At baseline the median (25th -75th percentile) VAS pain was 45 mm (26-60) in the HCQ group and 50 mm (25-63) in the placebo group. The mean (SD) total AUSCAN score was 5.2 (1.9) in the HCQ group and 5.0 (1.9) in the placebo group (0 - 10 scale). The mean (SD) total AIMS2-SF score was 3.7 (1.2) in the HCQ group and 3.9 (1.2) group (0 - 10 scale). After 24 weeks the median (25th -75th percentile) VAS pain was 36 mm (16-58) and 48 mm (23-62) in the HCQ and placebo groups respectively. The decreases in pain were not statistically significant within the groups. Also, no statistically significant difference was seen between the intervention and placebo group at any time point (t =0, 6, 12, 24 weeks) for VAS pain scores, AUSCAN total and subscales or AIMS-SF2 outcomes. Conclusions: This study shows that 24 weeks of treatment with HCQ in symptomatic hand OA did not reduce pain when compared to placebo. Also, no effect was observed in change of AUSCAN total and subscales scores or AIMS2-SF scores between both treatment groups. These results suggest that HCQ should not be prescribed in patients with primary hand OA with mild to moderate pain symptoms. Further investigation is required to determine the efficacy of HCQ in other hand OA phenotypes. Disclosure of Interest: None declared